Study of Changing Pattern of Bacterial Isolates in Neonatal Sepsis (Medical Forum Monthly, 2024)
ABSTRACTObjective: To identify the changing pattern of bacterial (aerobic) isolates of neonatal sepsisStudy Design: Observational studyPlace and Duration of Study: The study was conducted at the department of Microbiology, Basic Medical Science Institute of JPMC during the period of January 2009 December 2010. Materials and Methods: The blood samples were taken from babies admitted at National Institute of Child Health. The study included 200 babies between the ages of 1 to 30 days who were presumed to have sepsis on clinical grounds. Neonates who had already been given antibiotics prior to admission and those who had congenital anomaly were excluded. Two hundred (200) blood samples were processed for blood culture. In the laboratory, specimen were inoculated on differential and selective media accordingly. Gram`s staining and biochemical test were performed by standard techniques.Results: Out of 200 cases 96 had positive blood cultures of which 73 (76.04%) were gram negative and 23 (23.96%) were gram positive bacterial isolates. In this study Enterobacter cloacae was isolated as leading cause of neonatal sepsis in 23 cases followed by Escherichia coli in 17 cases, Klebsiella pneumoniae in 16 cases, Staphylococcus epidermidis in 15 cases, Pseudomonas aeruginosa in 11 cases, Staphylococcus aureus in 10 cases, Citrobacter freundii in 3 cases Neisseria meningitidis in 1 case, Listeria monocytogenes in 1 case, Haemophilus influenzae in 1 case and Non Typhoidal Salmonella in 1 case.Conclusion: Varying pattern of bacterial isolates causing neonatal sepsis warrants the need for continuous ongoing review of causative organisms. A periodic review of neonatal sepsis is important as it may help in detecting any change in the infecting organism. Therefore, purpose of present study was to describe bacterial isolate from blood culture and to observe the change in bacteriological pattern to provide prompt treatment for neonatal sepsis.